Three cultures, four hooves and one river: the Canadian river in Texas and New Mexico, 1848-1939 - Bickers, Margaret A. (Kansas State University, 2010)
During the period between 1848 and 1938, a combination of land-use changes and regional climatic alterations caused changes in the physical structure of the Canadian River. The Canadian River begins in the southern Rocky Mountains and flows south and then northeast across the High Plains of New Mexico and Texas. The Comanche Indians used the river as a transportation corridor, as a winter shelter for themselves and for their horse herds, as well as hunting the bison that visited the valley. The Comanches also valued the spiritual power, puha, found in the running water and on the mesas within the river’s lowlands. After the defeat of the Comanches in the Red River Wars and the destruction of the bison herds, New Mexican Hispanos moved their flocks of sheep into the valley and established settlements along the tributary streams. These settlers practiced “extensive” land use, drawing from a broad array of the valley’s resources and using them comparatively lightly in ways that drew from older Spanish laws and customs. The enclosure of parts of the valley by Anglo-Texan ranchers drove the Hispanos out of the Canadian watershed in Texas, although access to the open range in New Mexico allowed other Hispanos to retain their settlements. Corporations including the Capitol Lands Syndicate and Prairie Cattle Company introduced large numbers of cattle to the region at the same time that regional rainfall patterns shifted. This combination of heavy grazing and altered precipitation patterns led to erosion in the uplands that caused changes in the physical structure of the Canadian River. After 1903, the arrival of railroads into eastern New Mexico accelerated the development of dry-land farms in both states. Increasing calls for damming and controlling the Canadian led to the first interstate Canadian River Compact in 1928. The advent of a severe drought in the 1930s and the Great Depression led to federal resources becoming available and the first dam was built on the stream, ending the era of the free-flowing river and again starting physical changes to the Canadian.
Keywords: Canadian River; Ranching; Hispano; fluvial geomorphology; History, United States (0337)